ChemInform Abstract: Thermal [2 + 2]‐Cycloaddition of Ketenes with Chiral Enol Ethers: Route to Densely Substituted Cyclobutanones. Issue 44 (13th October 2016) - Rulliere, Pauline; Grisel, Julien; Poittevin, Clement; Cividino, Pascale; Carret, Sebastien; Poisson, Jean‐Francois
Abstract: An unprecedented [2 + 2] cycloaddition of in situ generated ketenes with 1‐(2, 4, 6‐triisopropylphenyl)ethyl substituted enol ethers provides a synthesis of cyclobutanones with good to excellent diastereoselectivity.